Devon Island Programs, 1972-1973 - Elcock, Ward; Hoyer, Michiel; Barrett, Paul; Schulten, Ronald (ARCTIC, 1973)
From April 1972 through the 1973 field season, the Arctic Institute's research base on the northeast coast of Devon Island (75°40'N, 84°40'W) will be the seat of operations for scores of investigators and their field assistants. The major research program continues to be a large integrated tundra ecosystem study sponsored by the Canadian International Biological Program (IBP). The Base Camp is also being used by groups of researchers from the Canadian Wildlife Survey, and from the Polar Continental Shelf Project. The two AINA-sponsored projects are summarized below. . During the summer of 1972, and the winter of 1972-73, the camp was used as a communications centre, and for providing other assistance to research stations established on Coburg Island and on the Carey Islands (Greenland) which are part of the Institute's North Water Project. . [1] ECOLOGICAL STUDIES OF SEDGE-DOMINATED MEADOW TUNDRA. During the 1972 field season studies were continued on the ecology of sedge-dominated meadows. . Studies of rhizome behaviour were continued. Complete systems were excavated and collected at five locations. Rhizome growth was monitored on selected individual plants. . Population characteristics of sedges invading small ponds and drained lake systems were further investigated. Three-and-a-half weeks were spent at the National Museum of Natural History camp on Bathurst Island. . six sedge meadows were selected and analysed for comparison with the Devon Island meadows. Five permanent plots were also established and mapped and populations of Carex stans collected for both seed and morphological measurements. A project to investigate the revegetation of vehicle-disturbed sedge meadows with native Carex species was also initiated. . Analysis of plantings of Carex stans as well as natural revegetation in some blocks will be monitored in following seasons. . [2] VEGETATION STUDIES ON THE INTERIOR PLATEAU. . A 2.4 km transect was placed east from the Plateau margin to the interior. The transect crossed a number of habitats, ...